Astroglial calcium signalling: what it could tell us - Rusakov, Dmitri (Henry Stewart Talks, 2022)
Astrocytes, Astroglia, Glia, Calcium signalling, Three Dimensional Electron Microscopy, Alexa Fluor 594, Oregon Green 488 BAPTA-1, Monitoring resting calcium, Fluorescence recordings, Fluorescence lifetime imaging microscopy, Astrocyte model